Effect of crude plant extracts from some Oaxacan flora on two deleterious fungal phytopathogens and extract compatibility with a biofertilizer strain - Lira-De León, Karla I.; Ramírez-Mares, Marco V.; Sánchez-López, Vladimir; Ramírez-Lepe, Mario; Salas-Coronado, Raúl; Santos-Sánchez, Norma F.; Valadez-Blanco, Rogelio; Hernández-Carlos, Beatriz (Frontiers in Microbiology, 2014)
The antimicrobial activity of 12 plant extracts was tested against the phytopathogens Alternaria alternata and Fusarium solani. In addition, the compatibility of the extracts toward Bacillus liqueniformis, a biofertilizer and a non-target microorganism, was assessed. Plants tested belong to the Euphorbiaceae, Asteraceae, Crassulaceae, Rubiaceae, Convolvulaceae, Verbenaceae, Orchidaceae, Nyctaginaceae, Boraginaceae, and Tiliaceae families and were collected in the State of Oaxaca. The antifungal activity of the plant extracts (50–100 mg/mL) against A. alternata and F. solani, was determined by measuring the mycelium radial growth and obtaining the minimum inhibitory concentration (MIC) of fungal growth. In addition, with the aim of finding plant extracts which are compatible with a B. licheniformis biofertilizer strain and to test the non-toxic nature of the treatments, the toxicity of the extracts toward this strain was evaluated using the agar diffusion method. Azoxystrobin (12 μg) and chloramphenicol (30 μg) were used as positive controls for the pathogens and for the non-target bacteria, respectively. Plant extracts inhibited fungal growth in the ranges of 0.76–56.17% against F. solani and 2.02–69.07% against A. alternata. The extracts of Acalypha subviscida, Ipomoea murucoides, Tournefortia densiflora and Lantana achyranthifolia showed MIC values between 5.77–12.5 mg/mL for at least one of the fungal species. The best treatment, Adenophyllum aurantium, exhibited a maximum inhibition for both F. solani (56.17%, MIC = 7.78 mg/mL) and A. alternata (68.64% MIC = 7.78 mg/mL), and resulted innocuous toward B. licheniformis. Therefore, this plant has an outstanding potential for the agroecological control of fungal phytopathogens in industrial crops.